Tinjauan Yuridis Persaingan Usaha Tidak Sehat Terhadap Usaha Besar dengan UMKM dalam Perspektif UU No. 20 Tahun 2008 (Studi Kasus Putusan Perkara Nomor 02/KPPU-K/2020) - Irma, Febriana; Gunadi, Ariawan (Universitas Ekasakti, 2023)
This research discusses the judicial review Unfair Business Competition Against Large Businesses and MSMEs in the Perspective of Law no. 20 of 2008. The primary focus of the study is the violation of Article 35 paragraph (1) of Law No. 20 of 2008 concerning Micro, Small, and Medium Enterprises, which prohibits